Degenerate Foliations in Sasakian Semi-Riemannian Manifolds - Cătălin Angelo IOAN (Acta Universitatis Danubius: Oeconomica, 2005)
In the Semi-Riemannian case we do not have the liability of the existence of such a metric being a difference from the Riemannian case. ASemi-Riemannian manifold provided with a normal contact metric structure is called Sasakian manifold.